Associative-memory representations emerge as shared spatial patterns of theta activity spanning the primate temporal cortex - Kiyoshi Nakahara (Nature Portfolio, 2016)
Episodic or declarative memory is thought to be encoded in the ensemble firing of spatially distributed neurons. Here the authors use high-density electrical recordings to show that some areas in the primate temporal cortex develop patterns of theta activity that are similar for pairs of remembered objects.